APPLYING DISCOURSE ANALYSIS IN ESP CLASSROOMS: BENEFITS AND CHALLENGES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
English for Specific Purposes (ESP) has gained prominence in language education due to its targeted approach in meeting learners’ professional or academic needs. Discourse Analysis (DA), the study of language beyond the sentence level, offers a powerful framework for enhancing ESP instruction. This paper explores the application of discourse analysis in ESP classrooms, highlighting its pedagogical benefits and identifying the practical challenges it presents. Through an examination of current literature and classroom practices, this study aims to provide educators with insights into how discourse analysis can be effectively integrated into ESP curricula.